Transient ureteric obstruction following pelvic floor reconstruction. Issue 5 (13th May 2021) - Beamer, Liam Joseph; Neary, Sarah; McCormack, Thomas; Ankers, David
Abstract : We describe the first reported case of transient distal ureteric obstruction attributed to post-surgical oedema in a patient with a solitary kidney. This occurred following combined pelvic floor repair and sacrospinous fixation for recurrent pelvic organ prolapse and manifested clinically as anuria, radiological hydroureter and acute kidney injury in the postoperative period. The transient nature of this obstruction, which was managed by a temporary percutaneous nephrostomy, indicates that it was caused by ureteric compression secondary to soft tissue oedema following surgery. We highlight the importance of this potential complication in females with a history of nephrectomy, unilateral renal tract anomalies or severely diminished renal reserve.